Promoção e percepção de aplicação da sustentabilidade nas Instituições de Ensino Superior brasileiras - Matias, Érika Pena Bedin (Universidade Federal de São Carlos, 2022)
Higher Education Institutions (HEIs) have occupied a distinctive role in society: they are predisposed to be at the forefront of social change and to deal with problems. In this context, the aim of this work was to investigate how the theme of sustainability is dealt with and the application of in HEIs. To achieve this objective, the work proposed to explore how sustainability in HEIs was addressed in the literature, to evaluate the selected publications, to integrate the dimensions of sustainability to the purpose activity of HEIs and how sustainability is operationalized in Brazilian HEIs. As results and discussion, the published articles were identified, with relevance and comprehensiveness and the main types, methodologies, scales, dimensions and approaches were analyzed. In addition to proposing the integration of the dimensions of sustainability with the end-activity of Brazilian HEIs, by means of structural equation modeling. Finally, the evaluation of the application of sustainability demonstrated that although there are constant efforts by both public and private HEIs, sustainability still reaches low levels of application in most of them. Future work needs to conduct the assessment in a multinational context and better investigate the interaction between sustainability in public and private HEIs.

Las Instituciones de Educación Superior (IES) han ocupado un papel distintivo en la sociedad: están predispuestas a estar en la vanguardia del cambio social y a ocuparse de los problemas. En este contexto, el objetivo de este trabajo fue investigar cómo se trata el tema de la sostenibilidad y su aplicación en las IES. Para alcanzar este objetivo, el trabajo se propuso explorar cómo se aborda la sostenibilidad en las IES en la literatura, evaluar las publicaciones seleccionadas, integrar las dimensiones de la sostenibilidad a la actividad de propósito de las IES y cómo se operacionaliza la sostenibilidad en las IES brasileñas. Como resultados y discusión, se identificaron los artículos publicados, con relevancia y alcance y se analizaron los principales tipos, metodologías, escalas, dimensiones y enfoques. Además de proponer la integración de las dimensiones de la sostenibilidad con el propósito-actividad de las IES brasileñas, por medio de un modelo de ecuaciones estructurales. Por último, la evaluación de la aplicación de la sostenibilidad demostró que, aunque existen esfuerzos constantes por parte de las IES tanto públicas como privadas, la sostenibilidad todavía alcanza niveles bajos de aplicación en la mayoría de ellas. Los trabajos futuros deben realizar la evaluación en un contexto multinacional e investigar mejor la interacción entre la sostenibilidad en las IES públicas y privadas.

Les établissements d'enseignement supérieur (EES) occupent un rôle particulier dans la société : ils sont prédisposés à être à l'avant-garde du changement social et à traiter les problèmes. Dans ce contexte, l'objectif de ce travail était d'étudier la manière dont le thème de la durabilité est abordé et appliqué dans les établissements d'enseignement supérieur. Pour atteindre cet objectif, le travail a proposé d'explorer comment la durabilité dans les EES a été abordée dans la littérature, d'évaluer les publications sélectionnées, d'intégrer les dimensions de la durabilité à l'activité de finalité des EES et comment la durabilité est opérationnalisée dans les EES brésiliens. Comme résultats et discussion, les articles publiés ont été identifiés, avec leur pertinence et leur portée, et les principaux types, méthodologies, échelles, dimensions et approches ont été analysés. En plus de proposer l'intégration des dimensions de durabilité avec l'objectif-activité des EES brésiliens, au moyen d'une modélisation d'équation structurelle. Enfin, l'évaluation de l'application de la durabilité a montré que, malgré les efforts constants des établissements d'enseignement supérieur publics et privés, la durabilité atteint encore de faibles niveaux d'application dans la plupart d'entre eux. Les travaux futurs devront mener l'évaluation dans un contexte multinational et mieux étudier l'interaction entre la durabilité dans les EES publics et privés.
Promotion and perception of sustainability application in Brazilian Higher Education Institutions
Promoción y percepción de la aplicación de la sostenibilidad en las instituciones de educación superior brasileñas
Keywords: Sustentabilidade; Instituições de Ensino Superior; Modelagem de Equações Estruturais; Sustainability; Higher Education Institutions; Structural Equation Modeling; Sostenibilidad; Instituciones de Educación Superior; Modelización de ecuaciones estructurales; Durabilité; Institutions d'enseignement supérieur; Modélisation par équations structurelles; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO; CIENCIAS SOCIAIS APLICADAS; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO; OUTROS